Identifying instruments to quantify financial management skills in adults with acquired cognitive impairments. Issue 1 (2nd January 2016) - Engel, Lisa; Bar, Yael; Beaton, Dorcas E.; Green, Robin E.; Dawson, Deirdre R.
ABSTRACT: Introduction : Financial management skills—that is, the skills needed to handle personal finances such as banking and paying bills—are essential to a person's autonomy, independence, and community living. To date, no comprehensive review of financial management skills instruments exists, making it difficult for clinicians and researchers to choose relevant instruments. The objectives of this review are to: (a) identify all available instruments containing financial management skill items that have been used with adults with acquired cognitive impairments; (b) categorize the instruments by source (i.e., observation based, self-report, proxy report); and (c) describe observation-based performance instruments by populations, overarching concepts measured, and comprehensiveness of financial management items. Objective (c) focuses on observation-based performance instruments as these measures can aid in situations where the person with cognitive impairment has poor self-awareness or where the proxy has poor knowledge of the person's current abilities. Method : Two reviewers completed two systematic searches of five databases. Instruments were categorized by reviewing published literature, copies of the instruments, and/or communication with instrument authors. Comprehensiveness of items was based on nine key domains of financial management skills developed by the authors. Results : A total of 88 discrete instruments were identified. Of these, 44 were categorized as observation-based performance and 44 as self- and/or proxy-reports. Of the 44 observation-based performance instruments, 8 had been developed for acquired brain injury populations and 24 for aging and dementia populations. Only 7 of the observation-based performance instruments had items spanning 6 or more of the 9 financial management skills domains. Conclusions : The majority of instruments were developed for aging and dementia populations, and few were comprehensive. This review provides foundation for future instrument psychometric and clinimetric reviews. It a necessary first step in providing information to support decision making for clinicians and researchers selecting financial management skills instruments.